Torture, Play, and the Black Experience - Trammell, Aaron (G|A|M|E Games as Art, Media, Entertainment, 2020)
This essay considers how the experience of Black folk descended from slaves in North America helps us to rethink a definition of play that has been largely informed by scholars and philosophers working within a White European tradition. This tradition of play, theorized most famously by Dutch Art Historian Johan Huizinga, French Sociologist Roger Caillois, Swiss Psychologist Jean Piaget, and New Zealander Brian Sutton-Smith reads play in a mostly positive sense and asserts that certain practices, namely torture, are taboo and thus cannot be play. I argue that this approach to play is short-sighted and linked to a troubling global discourse that renders the experiences of Black, Indigenous, and People of Color (BIPOC) invisible. In other words, by defining play only through its pleasurable connotations, the term holds an epistemic bias towards people with access to the conditions of leisure. Indeed, torture helps to paint a more complete picture where the most heinous potentials of play are addressed alongside the most pleasant, yet in so doing the trauma of slavery is remembered. In rethinking this phenomenology, I aim to detail the more insidious ways that play functions as a tool of subjugation. One that hurts as much as it heals and one that has been complicit in the systemic erasure of BIPOC people from the domain of leisure.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

Games Studies India Adda #10: Aaron Trammell - Game Studies India Adda (Game Studies India Adda, 2021)
Repairing Play: Toward A Black Phenomenology of Play In this talk I offer the term "repairing play" or play that both repairs the damages wrought by colonialism, and is itself a form of reparations, in an effort to consider how we might advance an understanding of play that is inclusive of BIPOC people. I focus in on the Black American experience in order to better theorize a moment of repair, and consider how torture is memorialized in play through song. I also will draw on examples from Black artists and game designers in order to help show how their work in repairing play draws from the tradition of Black radical aesthetics. Bio: Aaron Trammell is an Assistant Professor of Informatics and Core Faculty in Visual Studies at UC Irvine. He writes about how BIPOC experience the games they play. Specifically, he is interested in how games and play further values of white privilege and hegemonic masculinity in geek culture. Aaron's work has been cited in Wired and featured on National Public Radio. It has been published in Game Studies, Games & Culture, New Media & Society, and G|A|M|E. He is the Editor-in-Chief of the journal Analog Game Studies and the Multimedia editor of the Sounding Out!
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); _Nettoyé